HEUTAGOGY APPROACH IN SUPPORTING ONLINE LEARNING SYSTEM AND STUDENTS’ LEARNING MOTIVATION - Rinaldi Rinaldi; Deni Wahyuni; Mohd. Isa Hamzah (Unversitas Negeri Padang, 2024)
Education has explored and used a variety of approaches in an effort to increase the learning and teaching process for adult learners. Online learning requires learners to be self-motivated and disciplined since they have more control over their schedule and learning environment. Some learners may struggle with staying motivated, managing their time effectively, or maintaining focus without the structure and accountability of a traditional classroom. Self-discipline and motivation are key factors in achieving success in online learning. Here are some strategies to foster self-discipline and maintain motivation in an online learning environment. Heutagogy has recently become a learning method for adult learners. In the heutagogy approach, students are highly autonomous and emphasize the development of students' abilities, with the goal of cultivating students who are ready to face the complexities of today's work world. This method implements a learning approach to an online learning system using the internet and other new technologies to develop and provide teaching methods. Based on recent literature reviews, this article discusses the heutagogy approach in supporting online learning systems. This article provides a basis for using heutagogy as a theory to discuss and study the use of new technologies in online learning. By acknowledging and actively addressing these challenges, institutions and educators can enhance the quality and effectiveness of online learning experiences and better support their students in achieving their learning goals.